Pola Pembelajaran Agama Islam di Madrasah dalam Perspektif Pendidikan Holistik: Studi Kasus di Madrasah Aliyah Negeri 3 Sleman Yogyakarta - Ahmad, Zainal Arifin (Yayasan Sukma, 2018)
This research aims at investigating the pattern of Islamic learning process at Yogyakarta-based Islamic senior high school-3 from holistic learning perspective. The research adopts qualitative approach. The research shows that the pattern of the Islamic learning process at the Islamic senior high school implemented in the unity of Islamic education curriculum with three main inseparable components, i.e. intra-curricular, extracurricular and hidden-curricular, has accommodated holistic learning principles. The accommodation can be evaluated from the implementation of basic holistic learning principles comprising of interconnectedness, wholeness and being. In spite of this accommodation, the research has found some weaknesses in the Islamic learning processs. First, the development of the five-level of learners potencies as envisioned in holistic learning, i.e. personal, community, social, planetary and cosmic, has not been formulated explicitly in the curriculum and lesson plan. The existing formulation only respects to the development of six dimensions of learners potencies, i.e. physical, emotional, intellectual, social, aesthetic, and spiritual. Second, the intra-curricular learning process is still more oriented to teaching for the test and less oriented to teaching for the whole task. Third, the subject matter of Islamic learning curriculum, i.e. al-Qur’an-Hadis, Akidah-Akhlak, and Fikih have not been integrated as a single unit. The three subject matters still stand on their own theme, and have not been integrated as a single unit. The research has successfully mapped out the characterizing pattern of quality development of Islamic learning process seen from the perspective of holistic learning at the madrasah.[Penelitian ini bertujuan untuk mengungkapkan pola pembelajaran agama Islam di MAN 3 Sleman Yogyakarta ditinjau dari perspektif pembelajaran holistik. Penelitian ini menggunakan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa proses pembelajaran agama Islam di MAN 3 Sleman Yogyakarta yang diimplementasikan dalam kesatuan program pembelajaran intrakurikuler, ekstrakurikuler, dan hidden curricular secara umum telah mengarah kepada pola pembelajaran holistik. Dikatakan demikian karena dalam penerapan kesatuan tiga program pembelajaran tersebut ditemukan adanya penerapan tiga prinsip dasar pembelajaran holistik yang meliputi connectedness, wholeness, dan being. Hanya saja, dalam proses pembelajaran agama Islam tersebut masih terdapat beberapa kelemahan. Pertama, secara konseptual, pengembangan lima level potensi peserta didik (personal, komunitas, sosial, planetari, dan kosmis) sebagaimana dicanangkan dalam pembelajaran holistik belum terumuskan secara eksplisit dalam kurikulum maupun dalam perencanaan pembelajaran agama Islam. Rumusan yang ada hanya berkenaan dengan pengembangan enam dimensi potensi peserta didik (fisik, emosi, intelektual, sosial, estetika, dan spiritual). Kedua, proses pembelajaran agama Islam intrakurikuler masih lebih dominan berorientasi pada teaching for the test dan kurang berorientasi pada teaching for the whole task. Ketiga, materi pelajaran agama Islam intrakurikuler yang meliputi Akidah-Akhlak, al-Qur’an-Hadis, dan Fikih masih merupakan materi pelajaran yang berdiri sendiri-sendiri dan belum terintegrasi sebagai satu kesatuan untuk dapat memberikan kemampuan kepada peserta didik dalam melakukan tugas-tugas yang bersifat kompleks dan menyeluruh (whole task). Penelitian ini memberi kontribusi dalam memetakan karakteristik pola proses pembelajaran agama Islam di madrasah ditinjau dari perspektif pembelajaran holistik.]